Pengaruh Profitabilitas, Solvabilitas, Likuiditas, Aktivitas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar Di BEI Periode 2016-2020 - Erine Sulistiana; R. Gatot Heru Pranjoto (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study aims to determine and analyze the effect of Profitability, Solvency, Liquidity, Activity, and Firm Size on firm value in food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method used is purposive sampling method and obtained as many as 15 companies. The technique used in this research is multiple linear regression analysis and uses quantitative data. Based on the research results show that: 1) Profitability has a significant positive effect on firm value; 2) Solvency has a significant positive effect on firm value; 3) Liquidity has a significant positive effect on firm value; 4) Activities have a significant positive effect on firm value; 5) Firm size has a significant positive effect on firm value; 6) Profitability, Solvency, Liquidity, Activity, and Firm Size together have a significant positive effect on firm value.